The Integration of Pangadereng Values in the Bugis Bone Community from the Perspective of Maqashid al-Syari'ah: A Conceptual-Philosophical Study - Tahir, Tarmizi; Abdallah, Alaa Nour Beshry; Dasmarianti (Al-Bayyinah, 2025)
This study is motivated by the need to formulate the philosophical legitimacy of local wisdom within the framework of universal Islamic law. This conceptual and philosophical research aims to connect the Pangadereng ethical system of the Bugis Bone community—consisting of five core elements (Ade’, Bicara, Rapang, Wari’, and Sara’)—with the universal objectives of Maqāṣid al-Sharī‘ah. The study employs an expanded Maqāṣid framework that includes eight dimensions of protection, notably environmental sustainability (al-bi’ah) and state stability (al-daulah), to identify points of convergence between local ethical values and Islamic legal objectives. Using a qualitative descriptive approach and value-based hermeneutic analysis, the findings indicate that Pangadereng represents a coherent local ethical system that substantively aligns with the principles of Maqāṣid al-Sharī‘ah. Philosophically, Sara’ functions as a normative reference related to the protection of religion (ḥifẓ al-dīn), while Ade’ and Wari’ contribute significantly to social order, environmental sustainability (ḥifẓ al-bi’ah), and state stability (ḥifẓ al-daulah) as forms of collective public benefit (maṣlaḥah). This study makes a theoretical contribution to the development of a more inclusive and contextual Maqāṣid discourse by positioning local wisdom as a crucial philosophical foundation, complementing purely textual legal approaches.